The Relationship Between Work Fatigue and Work Stress Among Kawangkoan, Sonder, Tompaso (KST) Truck Driver Community - Panambunan, Dela; Mandagi, Chreisye K.F; Asrifuddin, Afnal (Journal of Literacy and Education, 2025)
Work-related fatigue and work-related stress are closely linked and can impact employee performance. Work-related fatigue can lead to poor performance, reduce worker quality, and have negative impacts. This research aims to determine the relationship between work fatigue and work stress among truck drivers in the Kawangkoan, Sonder, Tompaso truck driver community (KST). The research uses this study as an analytical study with a cross-sectional research design. The research was conducted from December 2024 to February 2025. In this study, a total of 34 drivers were sampled. The research results show a relationship between work fatigue and work stress. The significance value is 0.000, which is less than 0.05 (p < 0.05), and the correlation coefficient is 0.694, indicating a positive correlation. This indicates a significant correlation between work stress and truck driver fatigue. Where work stress scores positively correlate with levels of work fatigue